Infrastructure as an aspect of quality of life and its influence on life satisfaction in small towns of the German region type central location - Gareis, Philipp; Diller, Christian; Winkler-Kühlken, Bärbel (Raumforschung und Raumordnung | Spatial Research and Planning, 2021)
According to most (inter)national studies, life satisfaction in small towns is higher than in other types of towns with more inhabitants. With a population survey in eight German cities, we examine the importance of the infrastructure as an aspect of quality of life and the accessibility of infrastructure for local life satisfaction and whether or not the factor of social cohesion has a stronger impact on life satisfaction. The results show a differentiated picture: First, the infrastructure offer, as an aspect of objectively measurable quality of life does not have the greatest impact on life satisfaction. The population of the small towns in central locations apparently takes advantage of the infrastructure offers of their neighbouring towns and other places. Somehow, they are very satisfied with life on site, despite a low level of satisfaction with the infrastructure. The study thus tends to confirm the borrowing size concept, according to which small towns in the surrounding area benefit from the functions of the core city. On the other hand, the two factors of social cohesion and satisfaction with the performance of the local administration are closely related to the individual life satisfaction on site. For further research, the question arises, as which factors can explain local common sense best and how this can be improved through political measures.
Keywords: Small town; Life satisfaction; Infrastructure; Case study analysis